Probiotics Bacillus licheniformis Improves Intestinal Health of Subclinical Necrotic Enteritis-Challenged Broilers - Kan, Liugang; Guo, Fangshen; Liu, Yan; Pham, Van Hieu; Guo, Yuming; Wang, Zhong (Frontiers in Microbiology, 2021)
Necrotic enteritis infection poses a serious threat to poultry production, and there is an urgent need for searching effective antibiotic alternatives to control it with the global ban on in-feed antibiotics. This study was conducted to investigate the effects of dietary Bacillus licheniformis replacing enramycin on the growth performance and intestinal health of subclinical necrotic enteritis (SNE)-challenged broilers. In total, 504 1-day-old Arbor Acres male chickens were selected and subsequently assigned into three treatments, including PC (basal diet + SNE challenge), PA (basal diet extra 10 mg/kg enramycin + SNE challenge), and PG (basal diet extra 3.20 × 109 and 1.60 × 109 CFU B. licheniformis per kg diet during 1–21 days and 22–42 days, respectively + SNE challenge). Results showed that B. licheniformis significantly decreased the intestinal lesion scores and down-regulated the Claudin-3 mRNA levels in jejunum of SNE-infected broilers on day 25, but increased the mucin-2 gene expression in broilers on day 42. In addition, B. licheniformis significantly up-regulated the mRNA levels of TRIF and NF-κB of SNE-challenged broilers compared with the control group on day 25 and TLR-4, TRIF compared with the control and the antibiotic group on day 42. The mRNA expression of growth factors (GLP-2 and TGF-β2) and HSPs (HSP60, HSP70, and HSP90) were up-regulated in B. licheniformis supplementary group on days 25 and 42 compared with group PC. LEfSe analysis showed that the relative abundance of Lachnospiraceae_UCG_010 was enriched in the PG group; nevertheless, Clostridiales_vadinBB60 and Rnminococcaceae_NK4A214 were in PA. PICRUSt analysis found that the metabolism of cofactors and vitamins, amino acid metabolism, and carbohydrate metabolism pathways were enriched, whereas energy metabolism, membrane transport, cell motility, and lipid metabolism were suppressed in B. licheniformis-supplemented groups as compared with the PC control. In conclusion, dietary supplementation of B. licheniformis alleviated the intestinal damage caused by SNE challenge that coincided with modulating intestinal microflora structure and barrier function as well as regulating intestinal mucosal immune responses.